A randomized trial to assess whether portal pressure guided therapy to prevent variceal rebleeding improves survival in cirrhosis. Issue 5 (30th March 2017) - Villanueva, Càndid; Graupera, Isabel; Aracil, Carles; Alvarado, Edilmar; Miñana, Josep; Puente, Ángela; Hernandez‐Gea, Virginia; Ardevol, Alba; Pavel, Oana; Colomo, Alan; Concepción, Mar; Poca, María; et al.
Abstract : Monitoring the hemodynamic response of portal pressure (PP) to drug therapy accurately stratifies the risk of variceal rebleeding (VRB). We assessed whether guiding therapy with hepatic venous pressure gradient (HVPG) monitoring may improve survival by preventing VRB. Patients with cirrhosis with controlled variceal bleeding were randomized to an HVPG‐guided therapy group (N = 84) or to a control group (N = 86). In both groups, HVPG and acute β‐blocker response were evaluated at baseline and HVPG measurements were repeated at 2‐4 weeks to determine chronic response. In the HVPG‐guided group, acute responders were treated with nadolol and acute nonresponders with nadolol+nitrates. Chronic nonresponders received nadolol+prazosin and had a third HVPG study. Ligation sessions were repeated until response was achieved. The control group was treated with nadolol+nitrates+ligation. Between‐group baseline characteristics were similar. During long‐term follow‐up (median of 24 months), mortality was lower in the HVPG‐guided therapy group than in the control group (29% vs. 43%; hazard ratio [HR] = 0.59; 95% confidence interval [CI] = 0.35‐0.99). Rebleeding occurred in 19% versus 31% of patients, respectively (HR = 0.53; 95% CI = 0.29‐0.98), and further decompensation of cirrhosis occurred in 52% versus 72% (HR = 0.68; 95% CI = 0.46‐0.99). The survival probability was higher with HVPG‐guided therapy than in controls, both in acute (HR = 0.59; 95% CI = 0.32‐1.08) and chronic nonresponders (HR = 0.48; 95% CI = 0.23‐0.99). HVPG‐guided patients had a greater reduction of HVPG and a lower final value than controls ( P < 0.05). Conclusion : HVPG monitoring, by stratifying risk and targeting therapy, improves the survival achieved with currently recommended treatment to prevent VRB using β‐blockers and ligation. HVPG‐guided therapy achieved a greater reduction in PP, which may have contributed to reduce the risk of rebleeding and of further decompensation of cirrhosis, thus contributing to a better survival. (Hepatology 2017;65:1693‐1707).